Implementation Of Interactive Methods In Improving The Professional Skills Of The Teacher Of Military Educational Institutions And Improving The Educational Process (Journal of Pedagogical Inventions and Practices, 2024)
this article provides a reflection on how improving the effectiveness of training by applying interactive methods to the learning process, depending on the types of training, the interactive methods used will work in mastering the materials.